Constructive activism in the dark web: cryptomarkets and illicit drugs in the digital 'demimonde'. Issue 1 (2nd January 2016) - Maddox, Alexia; Barratt, Monica J.; Allen, Matthew; Lenton, Simon
ABSTRACT: This paper explores activism enacted through Silk Road, a now defunct cryptomarket where illicit drugs were sold in the dark web. Drawing on a digital ethnography of Silk Road, we develop the notion of constructive activism to extend the lexicon of concepts available to discuss forms of online activism. Monitoring of the cryptomarket took place between June 2011 and its closure in October 2013. Just before and after the closure of the marketplace we conducted anonymous online interviews with 17 people who reported buying drugs on Silk Road (1.0). These interviews were conducted synchronously and interactively through encrypted instant messaging. Participants discussed harnessing and developing the technological tools needed to access Silk Road and engage within the Silk Road community. For participants Silk Road was not just a market for trading drugs: it facilitated a shared experience of personal freedom within a libertarian philosophical framework, where open discussions about stigmatized behaviours were encouraged and supported. Tensions between public activism against drug prohibition and the need to hide one's identity as a drug user from public scrutiny were partially resolved through community actions that internalized these politics, rather than engaging in forms of online activism that are intended to have real-world political effects. Most aptly described through van de Sande's (2015 ) concept of prefigurative politics, they sought to transform their values into built environments that were designed to socially engineer a more permissive digital reality, which we refer to as constructive activism.